Plasma expanders - Porrini, Claudio C (Cirugía del Uruguay, 1973)
1) Dextran deriva tes are excelent plasma expansors. Consequently they are indicated in conditions the prevention and treatment of hipovolemic. 2) They have two other biological effects which have clear indications: a) Improvement of microcirculation, Dextratrane 40.000. b) Antithrombotic effect, Dextrane 70.000. 3) Due to their action mechanism, hydroelectrolitic infusions should be infused at the same time in order to avoid depletion of the interstitial space. 4) The usual dose is 500 ml. It is not convenient to go beyond 1.000 ml.